A novel community-acquired MRSA clone, USA300-LV/J, uniquely evolved in Japan. (26th July 2020) - Takadama, Shunsuke; Nakaminami, Hidemasa; Kaneko, Hiroshi; Noguchi, Norihisa
Abstract: Background: USA300 [ST8-staphylococcal cassette chromosome mec type IVa (ST8-IVa)/arginine catabolic mobile element (ACME) positive] is a major Panton–Valentine leucocidin (PVL)-positive community-acquired MRSA (CA-MRSA) clone. In Japan, we identified USA300-like strains with characteristics (ST8-IVc/ACME negative) similar to those of USA300. Objectives: To reveal the evolution of the USA300-like strains. Methods: The whole-genome sequence of a USA300-like strain was determined and genome analysis was performed using Type Strain Genome Server, MUSCLE and progressiveMauve. Results: Genome-based phylogenetic analysis showed that the USA300-like strain is more similar to the USA300-Latin American variant (USA300-LV), which is a PVL-positive CA-MRSA clone identified in South America, than to USA300. Instead of the ACME, copper and mercury resistance mobile elements were located on the genome of the USA300-like strain. In addition, the USA300-like strain possessed a unique mobile genetic element, ICE 6013 . Therefore, we named this novel USA300-LV variant identified in Japan as USA300-LV/J. Conclusions: Our findings strongly suggest that a PVL-positive CA-MRSA USA300-LV/J clone originating from abroad has uniquely evolved and disseminated in Japan.